Green microalgae as substrate for producing Biofuels and chlorophyll in Biorefineries - Gonçalves, Bruna C. M. [UNESP]; Silva, Messias B. [UNESP] (Springer Nature, 2018)
In order to develop sustainable technologies with reduced impacts in an attempt to repair previously caused damages to the environment, green alternatives have been the focus of several researches nowadays. Technological advances have enabled an effective use of natural sources to obtain clean energy, thus reducing emissions of gaseous pollutants into the environment. In this context, biofuels are promising alternatives for regulating climate change caused by an increase in the greenhouse effect, whose negative impact has been considerably perceived over the years. The use of microalgae as raw material to obtain biofuels has been proved promising. Due to the rich composition of carbohydrates, lipids and various proteins, biofuels and bioproducts can be obtained from microalgal cells, thereby contributing to bring down the final cost of products within the concept of biorefineries. Thus, this chapter aims to identify the process variables that interfere in microalgae cultivation to produce biofuels and pigments, and their impact on microalgal cell composition. Information on the most widely used culture media and the most studied species for obtaining biofuels by focusing on biohydrogen, biodiesel and bioethanol have been assessed. Furthermore, the process for obtaining these biofuels was illustrated in a simplified form in order to provide a general overview for readers.
Keywords: Microalgae cultivation; Renewable energy; Third generation biofuel